Essentials of physical chemistry - Shillady, Donald (CRC Press, 2011)
"Particularly well-suited for students not pursuing a traditional chemistry curriculum, such as premedical and forensic science students, this book presents a stand-alone approach to teaching physical chemistry in a one-semester course, a current trend in undergraduate education. This new undergraduate textbook succeeds in inspiring a thorough understanding rather than merely exposing students to what they all too often perceive as a painful and confusing experience. The author includes real-world applications, worked examples, end-of-chapter problems, key solutions, thermodynamic data, and much more to assist in the teaching and learning of physical chemistry"--